Compreendendo a histologia pela análise da morfofuncionalidade da pele por meio de uma sequência didática realizada com alunos do ensino médio - Georgia Martins Ferreira e Silva (2022)
The biology teaching's educational scenario is still very based on theoretical classes in which students participate passively. Thus, educational practices need to be improved by establishing methodologies that can place the student as a protagonist in the search for knowledge. Teaching by the investigation is configured as a didactic approach in which the student is encouraged to develop hypotheses to solve problems proposed by the mediator, in this case, the teacher or coming from his interest. The present project aims at developing an investigative didactic sequence about histology using the study of the skin morphofunctionality with students from their freshman year of high school. They will be able to develop actions by learning actively through the evaluation, planning and interpretation of data and scientific phenomena evidence, stimulating the evolution of a critical sense and the relating science with the everyday life. For this goal, a didactic sequence is proposed. Beginning with the application of qualitative pre-evaluative tests with subsequent contextualization of aspects of the skin and its connection with the external environment, the students will be able to elaborate hypotheses and create methodologies capable of being employed and presented in the science fair template. Built from a theoretical framework, a Digital Booklet was developed as a product of this work. Through this Digital booklet, a didactic sequence will be available to other professionals, contributing as one more tool to the improvement of public education.